The Instigation of the Associations Between Melatonin, Circadian Genes, and Epileptic Spasms in Infant Rats - Wan, Lin; Shi, Xiu-Yu; Ge, Wen-Rong; Sun, Yu-Lin; Zhang, Shan; Wang, Jing; Hu, Lin-Yan; Zou, Li-Ping; Yang, Guang (Frontiers in Neurology, 2020)
Abstract Background: Infantile spasm (IS) is one of the most common catastrophic epilepsy syndromes in infancy. While adrenocorticotropic hormone (ACTH) is the first-line treatment for IS, it is evident that the seizures associated with IS exhibit a clear circadian rhythm; however, the precise mechanisms underlying such seizures remain unclear. Melatonin is an important amine hormone and is regulated by circadian rhythm. Circadian proteins, especially BMAL1 and CLOCK, and their target proteins PER and CRY, play key roles in circadian rhythm. This study explored the relationships between melatonin, genes associated with circadian rhythm and IS. Materials and Methods: Eighteen female rats were mated with nine male rats and 16 became pregnant. Twelve pregnant rats were subjected to prenatal stress by forced swimming in cold water from the day of conception. Rat pups produced by stressed mothers received an intraperitoneal injection of N-methyl-D-aspartate (NMDA) on the 13th day after birth and were divided into four groups: NMDA (15 mg/kg), NMDA+ACTH (20 IU/kg), NMDA+melatonin (55 mg/kg) and NMDA+ACTH+melatonin (n=36/group). Offspring from four dams that were not subjected to prenatal stress were used as controls. We then recorded latency and the frequency of flexion seizures. All offspring were sacrificed on the 14th day after birth and CLOCK, BMAL1, PER1, PER2, CRY1 and CRY2 expression was analyzed by western blotting, immunohistochemistry and immunofluorescence. Results: NMDA induced spasm-like symptoms in rats. ACTH and melatonin significantly increased seizure latency and significantly reduced the frequency of seizures (P<0.05). CLOCK, BMAL1, PER1, PER2, CRY1 and CRY2 expression was significantly lower in the NMDA group than the controls (P<0.05). ACTH significantly increased the expression of CLOCK, BAML1, PER1, and CRY1 (P<0.05) and melatonin significantly increased the expression of CLOCK, BMAL1, PER1, PER2, CRY1 and CRY2 (P<0.05) compared with those of the NMDA group. There were no significant differences in the expression of BMAL1, CRY2, PER1 and PER2 when compared between the NMDA+ACTH+melatonin and control groups (P>0.05). Conclusion: ACTH and melatonin significantly increased the expression of circadian genes and improved NMDA-induced seizures. The anticonvulsant effects of ACTH and melatonin are likely to involve regulation of the expression of these genes.